2009
DOI: 10.1093/hmg/ddp498
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic ALS has compartment-specific aberrant exon splicing and altered cell–matrix adhesion biology

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by progressive weakness from loss of motor neurons. The fundamental pathogenic mechanisms are unknown and recent evidence is implicating a significant role for abnormal exon splicing and RNA processing. Using new comprehensive genomic technologies, we studied exon splicing directly in 12 sporadic ALS and 10 control lumbar spinal cords acquired by a rapid autopsy system that processed nervous systems specifically for genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(126 citation statements)
references
References 76 publications
8
117
1
Order By: Relevance
“…The identification of these potential FUS-R521C target genes provides important insights into the dendritic and synaptic phenotypes in FUS-R521C mice and explain why BDNF can only partially restore the dendritic phenotype in neurons expressing FUS-R521C (Figure 8). The RNA-seq approach also reveals many target genes in the extracellular matrix assembly GO categories (GO:0005581, GO:0005201, GO:0005578, and GO:0031012) that have also been shown to be transcriptional targets of DNA damage response genes CSB and HDAC1 (43) and are frequently misregulated and misspliced in the motor neurons of SALS patients (54). Although these results are correlative, they raise the interesting possibility that the recruitment of FUS, HDAC1, and CSB may constitute a critical step in the repair of damaged DNA in FALS caused by FUS mutations and in SALS.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of these potential FUS-R521C target genes provides important insights into the dendritic and synaptic phenotypes in FUS-R521C mice and explain why BDNF can only partially restore the dendritic phenotype in neurons expressing FUS-R521C (Figure 8). The RNA-seq approach also reveals many target genes in the extracellular matrix assembly GO categories (GO:0005581, GO:0005201, GO:0005578, and GO:0031012) that have also been shown to be transcriptional targets of DNA damage response genes CSB and HDAC1 (43) and are frequently misregulated and misspliced in the motor neurons of SALS patients (54). Although these results are correlative, they raise the interesting possibility that the recruitment of FUS, HDAC1, and CSB may constitute a critical step in the repair of damaged DNA in FALS caused by FUS mutations and in SALS.…”
Section: Methodsmentioning
confidence: 99%
“…However, aberrant intron inclusion has not been reported in fALS patients. Interestingly, a study used exon arrays to probe changes in sporadic ALS patients and found aberrant splicing in cell adhesion and cell matrix genes (Rabin et al 2010). However, the exact nature of the missplicing was not determined, nor is it known whether Fus was mutated in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RNA profiling suggested direct induction of C1q complement components in laser-microdissected postmortem ALS motor neurons (26). With respect to ALS mouse models, our own recent laser microdissection-assisted RNA profiling of motor neurons isolated from two different SOD1 mutant ALS mouse lines (SOD1 G37R and SOD1…”
Section: Significancementioning
confidence: 99%